2014
DOI: 10.1111/1574-6941.12391
|View full text |Cite
|
Sign up to set email alerts
|

pH-dominated niche segregation of ammonia-oxidising microorganisms in Chinese agricultural soils

Abstract: Ammonia-oxidising archaea (AOA) are increasingly recognised as the primary mediators of soil ammonia oxidation, particularly in acidic soils. To explore the niche segregation of AOA and ammonia-oxidising bacteria (AOB) and the potential effect of this segregation on nitrification rates and the nitrogen cycle in Chinese agricultural soils, AOA and AOB amoA gene databases were established, and 454 high-throughput sequencing was used to investigate the key factors leading to the niche segregation of these two typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 51 publications
6
31
0
Order By: Relevance
“…Archaeal amoA abundance and the ratio of AOA/archaeal 16S rRNA increased significantly with increasing pH, indicating that pH plays an important role in controlling AOA abundance in acidic and neutral paddy soils. Moreover, the ratio of AOA/ AOB amoA gene copy numbers ranged from 1.91 to 1048, which was consistent the ratio of AOA/AOB in previous studies (Leininger et al 2006;Shen et al 2008;Hu et al 2014), implying that indicating that AOA may be the major members in aerobic ammonia oxidation in these paddy soils. Zhang et al (2012) also indicated that AOA have more prominent role in ammonia oxidation in acidic soils, which means that acidic condition is more beneficial to AOA than AOB.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Archaeal amoA abundance and the ratio of AOA/archaeal 16S rRNA increased significantly with increasing pH, indicating that pH plays an important role in controlling AOA abundance in acidic and neutral paddy soils. Moreover, the ratio of AOA/ AOB amoA gene copy numbers ranged from 1.91 to 1048, which was consistent the ratio of AOA/AOB in previous studies (Leininger et al 2006;Shen et al 2008;Hu et al 2014), implying that indicating that AOA may be the major members in aerobic ammonia oxidation in these paddy soils. Zhang et al (2012) also indicated that AOA have more prominent role in ammonia oxidation in acidic soils, which means that acidic condition is more beneficial to AOA than AOB.…”
Section: Discussionsupporting
confidence: 90%
“…Further analysis via CCA also illustrated that soil SOC, TN, and the ratio of C/N were correlated with AOA abundance and consistent with the previous studies (Li et al 2014;Wu et al 2011). The abundance of AOA rather than AOB was influenced by soil properties in these paddy soils, especially pH, indicating that AOA were more sensitive to soil characteristics (Hu et al 2014;Chen et al 2011).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…AOB, however, exhibited the opposite and the copy numbers and transcriptional abundance of AOB amoA genes were less than that of AOA by two orders of magnitudes . In most acid soils, the abundance of AOA was more than that of AOB, suggesting a greater adaptability of AOA to live in the acid environment (Gan et al, 2016;He et al, 2007;Hu et al, 2014;Leininger et al, 2006;Norman and Barrett, 2016;Stempfhuber et al, 2015). In a peaty soil with a pH value of 4.1, the abundance of AOB amoA genes was below the detection limit while the abundance of AOA increased as the incubation went on.…”
Section: Ph Leading To the Niche Segregation Of Aoa And Aobmentioning
confidence: 98%